Comparison of conventional and digital lectures and examinations with respect to the conditions after COVID-19 period – an example for a bachelor lecture on textile finishing - Boris Mahltig (Communications in Development and Assembling of Textile Products)
Due to the appearance of COVID-19, many lectures and examinations at universities are forced to digital formats. In the first post-pandemic semester again, the change from digital to conventional lectures was demanded. By this background the question arises, what is the better format for lecture and exam – digital or conventional? This question is discussed on the example of a bachelor lecture on textile finishing for the time period from 2019 to 2023. The combination of digital lecture and digital exam leads to strong participation numbers and by this to more successfully passing students. If the exam is done as conventional written text, the influence if the lecture is digital or conventional is weak. Also, the numbers of passing students or the finally achieved mark are mainly not dependent on the type of lecture format. Finally, it can be state that a digital lecture is more successful if there are also digital parts in the examination. Also, the return to conventional lectures and exams after the pandemic period is possible without influencing the student performance compared to pre-pandemic situation.